Capillary pressure-based measurement of dynamic interfacial tension in a spontaneous microfluidic sensor. Issue 20 (14th September 2022) - Deng, Boxin; Schroën, Karin; Steegmans, Maartje; de Ruiter, Jolet
Abstract : The EDGE tensiometer allows access to nearly the full range of dynamic interfacial tension at relevant time scales for both droplet and bubble interfaces. Abstract : The size of droplets and bubbles, and the properties of emulsions and foams strongly depend on dynamic interfacial tension ( γ d ) – a parameter that is often inaccessible due to the very short time scales for droplet and bubble formation, and the inaccessibility of ( e.g., food) production lines. To solve this challenge, we developed a microfluidic tensiometer that can measure γ d by monitoring the formation time of both droplets and bubbles. Our tensiometer is a pressure-driven microfluidic device that operates based on the principle of a pressure balance: the formation of a droplet (or a bubble) is initialized when the Laplace pressure of the interface is decreased below the externally applied pressure, and this decrease is caused by a reduction in γ d that can be calculated from the applied pressure and the Young–Laplace equation. The decay of γ d due to surfactant adsorption can be followed at the characteristic time scale, which is dependent on surfactant type and concentration. For 0.05–1% wt sodium dodecyl sulfate (SDS), we were able to measure γ d at time scales down to 1 ms and 0.1 ms for droplet and bubble interfaces, respectively, at increasing applied pressures and SDS concentrations. Our tensiometer proves to be a simple, robust method that inherently allows access to nearly the full range of dynamic interfacial tension at relevant time scales.